Genome-wide association scan identifies a risk locus for preeclampsia on 2q14, near the inhibin, beta B gene - Johnson, M.; Brennecke, S.; East, C.; Göring, H.; Kent, J.; Dyer, T.; Said, J.; Roten, L.; Iversen, A.; Abraham, L.; Heinonen, S.; Kajantie, E.; et al. (2012)
Elucidating the genetic architecture of preeclampsia is a major goal in obstetric medicine. We have performed a genome-wide association study (GWAS) for preeclampsia in unrelated Australian individuals of Caucasian ancestry using the Illumina OmniExpress-12 BeadChip to successfully genotype 648,175 SNPs in 538 preeclampsia cases and 540 normal pregnancy controls. Two SNP associations (rs7579169, p = 3.58×10 -7, OR = 1.57; rs12711941, p = 4.26×10 -7, OR = 1.56) satisfied our genome-wide significance threshold (modified Bonferroni <5.11×10 -7). These SNPs reside in an intergenic region less than 15 kb downstream from the 3' terminus of the Inhibin, beta B (INHBB) gene on 2q14.2. They are in linkage disequilibrium (LD) with each other (r 2 = 0.92), but not (r 2<0.80) with any other genotyped SNP ±250 kb. DNA re-sequencing in and around the INHBB structural gene identified an additional 25 variants. Of the 21 variants that we successfully genotyped back in the case-control cohort the most significant association observed was for a third intergenic SNP (rs7576192, p = 1.48×10 -7, OR = 1.59) in strong LD with the two significant GWAS SNPs (r >0.92). We attempted to provide evidence of a putative regulatory role for these SNPs using bioinformatic analyses and found that they all reside within regions of low sequence conservation and/or low complexity, suggesting functional importance is low. We also explored the mRNA expression in decidua of genes ±500 kb of INHBB and found a nominally significant correlation between a transcript encoded by the EPB41L5 gene, ~250 kb centromeric to INHBB, and preeclampsia (p = 0.03). We were unable to replicate the associations shown by the significant GWAS SNPs in case-control cohorts from Norway and Finland, leading us to conclude that it is more likely that these SNPs are in LD with as yet unidentified causal variant(s).